1981
DOI: 10.1038/clpt.1981.150
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of α-difluoromethylornithine: An irreversible inhibitor of ornithine decarboxylase

Abstract: We gave alpha-difluoromethylornithine (DFMO), a selective, irreversible inhibitor of ornithine decarboxylase, to six health men in single intravenous doses of 5 and 10 mg/kg body weight and oral doses of 10 and 20 mg/kg. Plasma concentrations were monitored during the 24 hr after each dose. Urine was collected from 0 to 24 hr after drug and amount of unchanged drug excreted was determined. Peak plasma concentrations were reached within 6 hr after oral doses. The decay of the plasma concentrations followed firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Eflornithine is primarily eliminated by renal excretion (fraction excreted, Ͼ80%); no metabolites have been found, and the drug does not bind to plasma proteins (36). Its intravenous clearance is low (1.2 to 2 ml/min/kg) and is similar to the glomerular filtration rate (14,36,37). It is believed that these observed relationships, although not significant, might be a consequence of the influence of gender and body weight on the glomerular filtration rate (38).…”
Section: Discussionmentioning
confidence: 79%
“…Eflornithine is primarily eliminated by renal excretion (fraction excreted, Ͼ80%); no metabolites have been found, and the drug does not bind to plasma proteins (36). Its intravenous clearance is low (1.2 to 2 ml/min/kg) and is similar to the glomerular filtration rate (14,36,37). It is believed that these observed relationships, although not significant, might be a consequence of the influence of gender and body weight on the glomerular filtration rate (38).…”
Section: Discussionmentioning
confidence: 79%
“…Pharmacokinetic studies in humans have indicated that DFMO reaches levels of 0.5 to 0.6 mM in serum (1,13); with the much higher dosage regimens currently used in the treatment of pneumocystosis, inhibitory effects of DFMO against the organism should be well within achievable concentrations in serum.…”
Section: Discussionmentioning
confidence: 99%
“…It is also clear that the pharmacologic and toxicologic consequences of DFMO administration are directly related to depletion of polyamines engendered by the parent molecule. The oral bioavailability of 10 and 20 mg/kg doses in humans is 58% and 54% respectively (Haegele et al, 1981). Of the orally absorbed dose, 86% is recovered in the urine as unmetabolized drug; 81% of intravenously administered drug is also recovered as intact molecule in urine (Haegele et al, 1981).…”
Section: Metabolism Of Dfmomentioning
confidence: 99%